Gay and lesbian literature in the classroom: Can Gay themes overcome heteronormativity? - April M Sanders; Janelle B. Mathis (Journal of Praxis in Multicultural Education, 2013)
Lesbian, gay, bisexual, and transgender (LGBT) characters do exist in children’s and young adult literature, yet there is a lack of classroom exposure to such literature. Educational organizations have realized the need for dispelling prejudices about LGBT people by including such texts in the classroom as well as discussions regarding LGBT themes and characters in the books. Yet the practice of simply including diverse texts without discussing LGBT issues could cause greater marginalization for students because the silence regarding LGBT issues and characters encourages the practice of heteronormativity. This inquiry examined a range of children’s and adolescent books that could be used in classroom discussions to develop insight about LGBT themes and characters in order to understand if the texts were saturated with LGBT themes and characters to the point that teachers and students could not avoid the LGBT factors while reading.
Keywords: amériques; approches et analyses; discipline; hétérosexisme; identités LGBTQIA2+; pédagogie; ressource en ligne; régions géographiques; science de l'éducation; systèmes d'oppressions; thématiques; états-unis

L’inclusion de la diversité sexuelle à l’école : les enjeux pour les élèves lesbiennes, gais, bisexuels et en questionnement - Richard, Gabrielle; Chamberland, Line; Petit, Marie-Pier (Revue canadienne de l’éducation, 2013)
Cet article s'appuie sur les résultats d'une enquête qualitative menée auprès de 65 jeunes lesbiennes, gais, bisexuels et en questionnement (LGBQ) québécois qui ont témoigné de leurs expériences scolaires en lien avec l'homosexualité. Les entrevues visaient à rendre compte de la place de la diversité sexuelle dans les cours, à relever les façons dont est abordée cette thématique en classe, ainsi qu'à examiner les perceptions qu'ont les participants de ces moments de visibilité. Les jeunes LGBQ rapportent que les sujets relatifs à la diversité sexuelle sont rarement abordés à l'école, mais se souviennent avec force détails de chacune des mentions de ces sujets. Nombre d'entre eux rapportent une vive crainte d'être étiqueté comme homosexuel à l'occasion de telles séances, ou encore de faire l'objet de railleries homophobes par la suite.
Keywords: 2000 à aujourd'hui; 2000-2009; EDI; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; discipline; discours dominant; homophobie; hétérosexisme; identités LGBTQIA2+; périodes historiques; québec; ressource en ligne; régions géographiques; science de l'éducation; systèmes d'oppressions; systèmes éducatifs; thématiques; école; étude qualitative